Alterity: condition of community (Devenires, 2004)
We stan out in an attempt to understand what the thesis eumeneis élenchoi (goodwill refutation) may mean within the context of Gadamerian hermeneutics; in order to articulate various concepts of the complex notion of ‘dialogue’, taken into account to understand and conclude that what really supports the theoretical building (architecture) of the dialogical proposal is a specific notion of ‘alterity’. Thus, once alterity is constituted as a conceptual foundation, we state the problem of what is thought to be ‘the common’, necessary to all social thought. From this we draw a few consequences that seem relevant to us for political thought and, in particular, considering the importance of political thought hermeneutically informed.
Keywords: alterity; community; dialogue